SISTEM INFORMASI KEARSIPAN PADA PT. PERMATA GRAHA NUSANTARA (PGNMAS) - Artika Surniandari; Hilda Rachmi; Ria Septilinah (Jurnal Mantik Penusa, 2019)
The development of information technology (IT) has become a necessity.All levels of society such as companies, institutions and agencies are moved to move forward and use it, including in activities related to administration. One of the activities which is closely related to administration is the management of archives (letters). PT. PGNMAS still uses manual methods in managing its letter data. Therefore, this study aims to assist the work of employees through the design of a system that can include work from conceptualization, recording and archiving of letters. A system that can archive incoming and outgoing mail effectively and efficiently. This design uses the waterfall model and Adobe Dreamweaver 8 software. The design of this information system is the best solution to solve the problems that exist in this company so that the system runs more effectively and efficiently and the archiving system is now more conducive compared to the previous system.